Predictors of heart failure in children with congenital heart disease - Meily Elven Nora; Indah Kartika Murni; Sasmito Nugroho; Noormanto Noormanto (Paediatrica Indonesiana, 2022)
Background Heart failure continues to be a significant contributor to morbidity and mortality in children with congenital heart disease (CHD). Little is known about heart failure in children. Identifying predictors of heart failure in children with CHD can serve to guide preventive strategies to heart failure.